The Effect of Competence, Work Motivation and Compensation on the Performance of Employees of the Regional Civil Service Agency (BKD) of Sidoarjo Regency - Mochamad Zidny Fithon; Riyadi Nugroho (Sharia Oikonomia Law Journal, 2024)
This study aims to analyze the effect of competence, work motivation and compensation on the performance of employees of the Regional Civil Service Agency (BKD) of Sidoarjo Regency. The data in this study used quantitative research methods. In this study, data obtained in the t test (partial) showed that the competency variable had a partial influence on employee performance with a competency regression coefficient (X1) value of 2.823 and a work motivation regression coefficient (X2) value of 3.656 while compensation (X3) had a regression coefficient value of 3.092. The data from Test F obtained f count > f table which is 173.059 > 2.80 so that it can be concluded that the variables competence (X1), work motivation (X2), and compensation (X3) simultaneously have a positive and significant influence on variables tied to employee performance (Y). It is hoped that this research can be used as a guideline material in decision making for the leadership of the Regional Civil Service Agency (BKD) of Sidoarjo Regency and the government related to variables of competence (X1), work motivation (X2), compensation (X3) and employee performance (Y). This research is also expected to be able to provide insight, knowledge, and information about competence (X1), work motivation (X2), compensation (X3), and employee performance (Y) at the Regional Civil Service Agency of Sidoarjo Regency, for students, the community, and also BKD employees themselves.